Acupressure as a Complementary Nursing Intervention for Muscle Trauma Rehabilitation in Rural Farmers: A Quasi-Experimental Study - Aristawati, Evy; Rahmawati , Apriana; Huda, Nurul; Cahyono, Bagus Dwi (Tarqabin Nusantara Group, 2025)
Musculoskeletal pain is one of the most prevalent health conditions among adults, frequently leading to reduced functional capacity and diminished quality of life. Non-pharmacological interventions such as soft tissue manipulation have gained increasing attention as strategies to reduce analgesic dependence and promote functional recovery. This study aimed to evaluate the effectiveness of soft tissue manipulation in reducing pain and improving functional activity in patients with muscle trauma. A quasi-experimental pretest–posttest control group design was employed, involving 100 participants allocated into an intervention group (n = 50) and a control group (n = 50). Pain intensity was assessed using the Visual Analog Scale (VAS), while functional ability was measured using the Patient-Specific Functional Scale (PSFS). Data were analyzed using appropriate parametric and non-parametric tests, with Odds Ratio (OR) calculated to determine the likelihood of clinically meaningful improvement. The intervention group demonstrated a substantially greater reduction in pain (?VAS = 3.4) compared with the control group (?VAS = 1.1). A total of 76% of participants in the intervention group achieved clinically significant improvement, yielding an OR of 6.09, indicating a six-fold higher likelihood of improvement relative to controls. Functional scores also increased significantly following the intervention. These findings highlight soft tissue manipulation as an effective non-pharmacological approach for reducing musculoskeletal pain and enhancing functional activity, supporting its integration into clinical rehabilitation practice.